Effect of Coarse Aggregate Sources on the Compressive Strength of Various Grade of Nominal Mixed Concrete - Prajapati, Jeetendra; Karanjit, Sudip (Journal of Science and Engineering, 2019)
Various grades of nominal mix concrete from low to medium strength are being used in building construction works in Kathmandu Valley. The aim of the study was to investigate the source effect of various types of coarse aggregates on the compressive strength of different grade of nominal mix concrete. Here, 5 different types of coarse aggregates sources were selected (A-Panauti, B-Melamchi, C-Chaukidada, D-Khopasi and E-Kaaldhunga) based on field enquiry and questionnaire survey with suppliers and contractors. Majority of coarse aggregates were angular in shape with a few sub angular and flaky types. From physical test result, most of the coarse aggregates were found to be graded type with partial deviation from the gradation limitation of IS383:1970. Based on specific gravity and dry-rodded bulk density, coarse aggregates can be classified as medium weight aggregates. Mechanical test of aggregate shows all the aggregates are of medium strength with variation in mechanical properties among them. The next stage of study is related to determination of compressive strength. Total 90 concrete cubes of size 15 cm were made of 3 different grades of nominal mix M1 (1:2:4), M2 (1:2:3) and M3 (1:1.5:3) by weight. Water/cement ratio, cement, sand, water were kept constant for each mix ratio while only coarse aggregate sources were chosen as variable. Due to change in aggregate type only, variation in 28 days target compressive strength is found up to 47%. Sample C, D and E showed relatively higher 28 days compressive strength compared to Sample A and B. The results indicate that the coarse aggregate source has significant variation in the compressive strength of various grade of nominal mix concrete. The variation in compressive strength is relatively significant for lean mix concrete (1:2:4 & 1:2:3) compared to rich mix concrete (1:1.5:3). In terms of concrete cube failure mechanism, the cubes made of sample A & B failed by coarse aggregate crushing while the major failure mechanism in sample C, D & E was initiated by bond failure.